EFFECT OF INTANGIBLE ASSETS ON VALUE RELEVANCE: EVIDENCE FROM LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of Economics and Sustainability, 2020)
The increasing importance and role of intangible assets in today’s economic environment is a source of concern for scholars and accounting practitioners. As an attempt to explore the relevance of reported intangible assets, the study investigated the market value relevance of different intangible asset (intellectual properties, computer software cost, and goodwill) reported by listed manufacturing firms in Nigeria. To achieve the research objective, the study adopted a correlational research design. The study utilized secondary data extracted from the annual reports and accounts of manufacturing firms listed on the Nigerian stock exchange. The study concentrated on firms that reported components of intangible assets for six years (2013-2019). The model was estimated using the random effect regression technique. The findings revealed intellectual properties to be positively and significantly associated with the market value of listed manufacturing firms in Nigeria. However, goodwill was shown to have a negative and significant relationship with market value. Based on the findings, the study recommends, amongst others, that the management of manufacturing firms bring their expertise to develop innovative technologies and business adaptations, as well as direct policies that will improve brand names and trademarks and protect patents and other intellectual properties as they will impact the market price.Received 10th January 20. Revised 3rd April 20. Accepted 19th April 20.